Harnessing improved seed and mechanization for climate resilience : Report on the CIMMYT Seed and Mechanization Fairs 2023 - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2023)
The International Maize and Wheat Improvement Center (CIMMYT), successfully hosted the fourth edition of the Seed and Mechanization Fairs, running under the theme "Harnessing improved seed and mechanization for climate resilience." The fairs served as a strategic market and learning platform for smallholder farmers in the implementation districts of Mwenezi and Masvingo. The aim was to connect farmers with private seed sector and mechanization companies, while facilitating the adoption of drought-tolerant seed and tailor-made machinery.